The mediating role of hope in the relationship between purpose in life and anxiety: A cross-cultural analysis in university students - Esteban Moreno-Montero; Rodrigo Moreta-Herrera; Jose A. Rodas; Evelyn Cuesta-Andaluz; Diana Ximena Puerta-Cortés; Daniela Ferrufino-Borja; Daniel Oleas; Renzo Gismondi Diaz (PLoS ONE, 2025)
Objective To examine the direct effect of purpose in life (PIL) on anxiety and its indirect effect through hope in a sample of university students from Ecuador, Bolivia, and Colombia, while assessing the cross-national measurement equivalence of the mediation model. Method A descriptive, correlational, and cross-sectional study was conducted using Structural Equation Modelling (SEM) to test mediation effects and Multigroup Confirmatory Factor Analysis (MG-CFA) to assess measurement invariance. The sample included 1,459 university students from Ecuador, Colombia, and Bolivia. Results PIL, hope, and anxiety exhibited significant latent correlations and formed a well-fitted structural model. PIL had both a direct effect on anxiety in Colombia and an indirect effect through hope across all three countries. In Ecuador and Bolivia, full mediation was observed, whereas in Colombia, mediation was partial. PIL and hope together explained 20.1% of the variance in anxiety, though this percentage varied across countries. Measurement invariance analyses confirmed that the mediation model was structurally equivalent across cultures, but differences in effect sizes suggest cultural modulation in the relationship between PIL, hope, and anxiety. Conclusion Anxiety were associated with cognitive processes related to meaning-making and hope, supporting their role as protective psychological variables. However, cultural context modulates the strength of these relationships, highlighting the need for context-sensitive interventions.